Multifunctional Redox and Temperature-Sensitive Drug Delivery Devices - Piazza, Rodolfo Debone [UNESP]; dos Santos, Caio Carvalho [UNESP]; Pinto, Gabriel Cardoso; Lucena, Guilherme Nunes; Junior, Miguel Jafelicci [UNESP]; Marques, Rodrigo Fernando Costa [UNESP] (My University, 2024)
Despite recent advances in drug delivery systems and tissue engineering, several challenges still need to be overcome for these new technologies to reach patients. The number of new cancer cases is increasing yearly, and the future projection is frightening. Another major health concern is the rise of antibiotic-resistant bacteria. The uncontrolled and excessive use of antibiotics has allowed bacteria to undergo mutation processes, decreasing the efficiency of this sort of drug. Therefore, the development of new medical devices is a battle against time to prevent projections on the advancement of diseases from being reached. Given this scenario, redox-sensitive and temperature-sensitive drug delivery platforms show promising results in the release of bioactive molecules. This review covers the most recent advances involving devices obtained from inorganic and polymeric matrices and their structuring as scaffolds and 3D printing, focusing on their potentiality of redox and temperature sensitivity for biomedical applications. Graphical Abstract: (Figure presented.)
Keywords: Cancer therapy; Drug delivery; Glutathione; Reactive oxygen species; Redox-sensitive platforms; Temperature devices